Effects of a Water, Sanitation, and Hygiene Mobile Health Program on Diarrhea and Child Growth in Bangladesh: A Cluster-randomized Controlled Trial of the Cholera Hospital-based Intervention for 7 Days (CHoBI7) Mobile Health Program. (6th August 2020) - George, Christine Marie; Monira, Shirajum; Zohura, Fatema; Thomas, Elizabeth D; Hasan, M Tasdik; Parvin, Tahmina; Hasan, Khaled; Rashid, Mahamud-ur; Papri, Nowshin; Islam, Aminul; Rahman, Zillur; Rafique, Raisa; et al.
Abstract: Background: The Cholera Hospital-Based Intervention for 7 Days (CHoBI7) mobile health (mHealth) program was a cluster-randomized controlled trial of diarrhea patient households conducted in Dhaka, Bangladesh. Methods: Patients were block-randomized to 3 arms: standard message on oral rehydration solution use; health facility delivery of CHoBI7 plus mHealth (no home visits); and health facility delivery of CHoBI7 plus 2 home visits and mHealth. The primary outcome was reported diarrhea in the past 2 weeks collected monthly for 12 months. The secondary outcomes were stunting, underweight, and wasting at a 12-month follow-up. Analysis was intention-to-treat. Results: Between 4 December 2016 and 26 April 2018, 2626 participants in 769 households were randomly allocated to 3 arms: 849 participants to the standard message arm, 886 to mHealth with no home visits arm, and 891 to the mHealth with 2 home visits. Children <5 years had significantly lower 12-month diarrhea prevalence in both the mHealth with 2 home visits arm (prevalence ratio [PR]: 0.73 [95% confidence interval CI, .61–.87]) and the mHealth with no home visits arm (PR: 0.82 [95% CI, .69–.97]). Children <2 years were significantly less likely to be stunted in both the mHealth with 2 home visits arm (33% vs 45%; odds ratio [OR]: 0.55 [95% CI, .31–.97]) and the mHealth with no home visits arm (32% vs 45%; OR: 0.54 [95% CI, .31–.96]) compared with children in the standard message arm. Conclusions: The CHoBI7 mHealth program lowered pediatric diarrhea and stunting among diarrhea patient households. Clinical Trials Registration: NCT04008134. Abstract : In this trial, young children in diarrhea patient households receiving the CHoBI7 mobile health program had less stunting and diarrhea compared with those only receiving the standard recommendation on oral rehydration solution for dehydration.